Non-coeliac gluten sensitivity. (30th November 2012) - Anonymous,; Rostami, Kamran; Hogg-Kollars, Sabine
Abstract : This patient reflects on his 20 years of unexplained ill health with multiple symptoms before a chance conversation in an internet chat room led to his initial self diagnosis